Installation of -SO2F groups onto primary amides - Liu, Jing; Wang, Shi-Meng; Alharbi, Njud S.; Qin, Hua-Li (Beilstein Journal of Organic Chemistry, 2019)
A protocol of SO2F2-mediated installation of sulfonyl fluoride onto primary amides has been developed providing a new portal to sulfur(VI) fluoride exchange (SuFEx) click chemistry. The generated molecules contain pharmaceutically important amide and -SO2F moieties for application in the discovery of new therapeutics.
Keywords: N-fluorosulfonyl amides; primary amides; sulfuryl fluoride (SO2F2)